Resettled Iraqi Refugees in the United States - Keyel, Jared (Berghahn Books, 2023)
The American war against Iraq has caused hundreds of thousands of deaths and displaced millions of people. Between 20 March 2003 and 30 September 2017, more than 172,000 Iraqis resettled in the United States. This book explores the experiences of fifteen Iraqis who resettled in the US after 2003. It examines the long war against Iraq that began in 1991 and the decisions some Iraqis made to leave their homes and seek refuge in the United States. The book also delves into the possibilities for belonging and cultural exchange for this cohort of Iraqis and their political engagement with non-profit organizations, advocacy, and activism against the 2017 Travel Ban.